Integrated physiological and transcriptional dissection reveals the core genes involving nutrient transport and osmoregulatory substance biosynthesis in allohexaploid wheat seedlings under salt stress - Jun-fan Chen; Ying Liu; Tian-yu Zhang; Zheng-fu Zhou; Jin-yong Huang; Ting Zhou; Ying-peng Hua (figshare, 2022)
Abstract Background Soil salinization has become a global problem restricting the seed yield and quality of crops, including wheat (Triticum aestivum L.). Salinity significantly alters plant morphology and severely disrupts physiological homeostasis. Salt tolerance of wheat has been widely studied whereas core ion transporters responsive to salt stress remain elusive. Results In this study, the wheat seedlings were subjected to salinity toxicity for morpho-physiological and transcriptomic analysis of wheat salt tolerance. There was a inversely proportional relationship between salt concentrations and morpho-physiological parameters. Under the condition of 100 mM NaCl, the H2O2, O2−, MDA content and membrane permeability were significantly increased whereas the chlorophyll content was markedly decreased. Under salt stress, a larger proportion of Na+ was partitioned in the roots than in the shoots, which had a lower Na+/K+ ratio and proline content. Salt stress also obviously affected the homeostasis of other cations. Genome-wide transcriptomic analysis showed that a total of 2,807 and 5,570 differentially expressed genes (DEGs) were identified in the shoots and roots, respectively. Functionality analysis showed that these DEGs were mainly enriched in the KEGG pathways related to carbon metabolism, phenylalanine, and amino acid biosynthesis, and were primarily enriched in the GO terms involving proline metabolism and redox processes. The Na+ transporter genes were upregulated under salt stress, which repressed the gene expression of the K+ transporters. Salt stress also significantly elevated the expression of the genes involved in osmoregulation substances biosynthesis, and obviously affected the expression profiling of other cation transporters. Co-expression network analysis identified TaNHX6-D5/TaNHX4-B7 and TaP5CS2-B3 potentially as core members regulating wheat salt tolerance. Conclusions These results might help us fully understand the morpho-physiological and molecular responses of wheat seedlings to salt stress, and provide elite genetic resources for the genetic modification of wheat salt tolerance.
Keywords: Genetics; Plant Biology